If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7y + -13) + -4y = 9 Reorder the terms: 2(-13 + 7y) + -4y = 9 (-13 * 2 + 7y * 2) + -4y = 9 (-26 + 14y) + -4y = 9 Combine like terms: 14y + -4y = 10y -26 + 10y = 9 Solving -26 + 10y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 10y = 9 + 26 Combine like terms: -26 + 26 = 0 0 + 10y = 9 + 26 10y = 9 + 26 Combine like terms: 9 + 26 = 35 10y = 35 Divide each side by '10'. y = 3.5 Simplifying y = 3.5
| (x-5)(x+3)=y | | 6y+3=2y+23 | | 7.7x-3.3=27.5 | | -2x+4=2x+1-3x | | 4n^2-7n-9=0 | | 4a^2+2a-6=0 | | 10(1/2)= | | 12c^2-84c+147=0 | | 6+5x=994-6x | | 6k=10m-4 | | x=56/5 | | 8c^2-84c+147=0 | | 54x2y3/72x3y | | 6d=9d-5 | | 3.1a+2=6a-2(1+2.4a)+1.53 | | X-y=7x+1 | | graphx^2+8=-6x | | -5=v-14 | | 4(x+3)-2=6(x-1)-x | | 6(6x+3)=270 | | 5/4n-2n/7n-6 | | 25-5z=4z-20 | | 135/540 | | 3+4y=x+6-5y | | 5x^2+(x-9)=0 | | 6/15-3/x | | 45y(1-x)=3x | | 2k+21=45 | | 3k+6k=-8+9k | | 15x-6=9x-4 | | -2(7)-3(-10)-7(6)= | | c^3-343/c-7= |